Uptake of prevention of mother-to-child transmission of human immunodeficiency virus interventions among infected mothers attending health facilities in Mombasa County, Kenya - Musyoka, Jacques Ngumbao; Okwara, Florence Nafula; Yonge, Shadrack (International Journal Of Community Medicine And Public Health, 2024)
Background: The study was conducted in Mombasa County, Kenya, and aimed at the uptake of Prevention of Mother-to-Child Transmission interventions among HIV-infected mothers attending health facilities. A hospital-based cross-sectional study was used between May 2021 and October 2021, utilizing a self-administered structured questionnaire to collect data. The collected information was then analyzed using SPSS version 17 and STATA version 9.2. Methods: The study utilized a descriptive cross-sectional research design. Results: 84.8% of respondents exclusively breastfed their babies, and 77.3% received antiretroviral drugs (ARVs). Education level, being a housewife, and religion showed statistically significant associations with PMTCT service uptake (p<0.05). Additionally, 53.7% of participants demonstrated awareness of the importance of enrolling in PMTCT intervention services. The study highlighted high levels of knowledge among participants regarding PMTCT interventions, with 89.9% having correct knowledge of ARVs for children, 83.5% understanding the importance of counselling, 77.3% practicing modified infant feeding, and 85% acknowledging the necessity of delivering in a health facility. Knowledge of PMTCT components such as HIV counselling, ARV usage, facility-based delivery, and early diagnosis was significantly associated with the uptake of PMTCT interventions. Conclusions: Utilization of PMTCT services among postnatal HIV-positive mothers was high among postnatal HIV-positive women who embraced the PMTCT interventions. The respondents had average knowledge concerning PMTCT services. This study suggests supporting and encouraging related stakeholders to provide education about MTCT.